Recovery of Sudden Cardiac Death- Role of Chain of Survival: A Case Report - Cervantes-Navarro, José Edgar; Ayón-Aguilar, Jorge; López-Luna, Ernesto; Narváez-Acosta, Jander; Gutiérrez-Romero, Anita (Archives of Clinical and Medical Case Reports, 2020)
Sudden cardiac death consists in a sudden cardiac collapse or heart failure secondary to arrhythmia, which unexpectedly occurs within the first hour after the onset of symptoms. Fibrillation and ventricular tachycardia are two arrhythmias responsible for most sudden cardiac arrest events. Others arrhythmias that produce this is asystole and pulseless electrical activity. The backbone in the treatment of sudden cardiac death is the immediate activation of the Chain of Survival with de early implementation of CPR and defibrillation, thus improving the prognosis of survival of patients. The automated implantable cardioverter defibrillator is a device with a high chance of reverting events caused by these arrhythmias to a sinus rhythm. We report a case of a 40-year old man who presented symptoms 20 minutes before being admitted to emergency services. An electrocardiogram was obtained, showing presence of QRS complex overlap in DI, DII and aVF. A skull computerized axial tomography scan showed no evidence of cerebral edema or located injuries. An echocardiogram showed normal heart size, left ventricle ejection fraction of 70%, valves without injuries, and no data regarding pulmonary arterial hypertension. Five days after the cardiac arrest event, an AICD was implanted as primary prevention strategy.